A transgenic minipig model of Huntington's Disease - Baxa, Monika; Hruska-Plochan, Marian; Juhas, Stefan; Vodicka, Petr; Pavlok, Antonin; Juhasova, Jana; Miyanohara, Atsushi; Nejime, Tetsuya; Klima, Jiri; Macakova, Monika; Marsala, Silvia; Weiss, Andreas; et al. (Journal of Huntington's disease, 2013)
BACKGROUND: Some promising treatments for Huntington's disease (HD) may require pre-clinical testing in large animals. Minipig is a suitable species because of its large gyrencephalic brain and long lifespan. OBJECTIVE: To generate HD transgenic (TgHD) minipigs encoding huntingtin (HTT)1-548 under the control of human HTT promoter. METHODS: Transgenesis was achieved by lentiviral infection of porcine embryos. PCR assessment of gene transfer, observations of behavior, and postmortem biochemical and immunohistochemical studies were conducted. RESULTS: One copy of the human HTT transgene encoding 124 glutamines integrated into chromosome 1 q24-q25 and successful germ line transmission occurred through successive generations (F0, F1, F2 and F3 generations). No developmental or gross motor deficits were noted up to 40 months of age. Mutant HTT mRNA and protein fragment were detected in brain and peripheral tissues. No aggregate formation in brain up to 16 months was seen by AGERA and filter retardation or by immunostaining. DARPP32 labeling in WT and TgHD minipig neostriatum was patchy. Analysis of 16 month old sibling pairs showed reduced intensity of DARPP32 immunoreactivity in neostriatal TgHD neurons compared to those of WT. Compared to WT, TgHD boars by one year had reduced fertility and fewer spermatozoa per ejaculate. In vitro analysis revealed a significant decline in the number of WT minipig oocytes penetrated by TgHD spermatozoa. CONCLUSIONS: The findings demonstrate successful establishment of a transgenic model of HD in minipig that should be valuable for testing long term safety of HD therapeutics. The emergence of HD-like phenotypes in the TgHD minipigs will require more study.
Keywords: lentiviral transgenesis; mutant huntingtin; TR-FRET assay; DARPP32; proteiny nervové tkáně; spermatozoa; mRNA and protein expression; genetické vektory; protein huntingtin; Huntingtonova nemoc; In Situ Hybridization; Nerve Tissue Proteins; hybridizace in situ; Huntington's disease; Transduction, Genetic; geneticky modifikovaná zvířata; Female; Swine, Miniature; Transgenes; Blotting, Western; Lentivirus; zvířata; transgeny; transdukce genetická; Swine; large animal model; FISH analysis; Animals, Genetically Modified; Huntington Disease; ženské pohlaví; Male; minipigs; polymerázová řetězová reakce; miniaturní prasata; Polymerase Chain Reaction; immunohistochemistry; Huntingtin Protein; Genetic Vectors; AGERA assay; Animals; western blotting; mužské pohlaví; Disease Models, Animal; prasata; modely nemocí na zvířatech